Knowledge and healthcare-seeking behavior of family caregivers of children with pneumonia: A qualitative study in an urban community in Indonesia - Nyimas Heny Purwati; Yeni Rustina; Bambang Supriyatno (Belitung Raya Foundation, Indonesia, 2021)
Background: Childhood pneumonia is the leading cause of death. Family caregivers may have a poor understanding of pneumonia, especially related to prevention and treatment. It is crucial to understand country-specific knowledge and healthcare-seeking behaviors of caregivers of children with pneumonia before planning programmatic responses, particularly in an urban community where the culture-social economic status is diverse. Objective: This study aimed to describe the knowledge and healthcare-seeking behavior of family caregivers of children with pneumonia in Indonesia’s urban community. Methods: A descriptive qualitative study was conducted at a public hospital in Jakarta, Indonesia, from 10 December 2019 to 28 January 2020. Ten family caregivers of children with pneumonia were included, and a semi-structured interview was conducted for data collection. The audio recording was transcribed verbatim, and the data were analyzed using content analysis. Results: The emerged data indicated low knowledge of the family caregivers, especially mothers, which considered pneumonia a common cold only, and they failed to understand the risk of its transmission. Using traditional medicines was the first stage of healthcare-seeking behavior. If the symptoms worsened, the caregivers brought their children to the nearest health center. If there was no change in the symptoms, they headed to the hospital. The health center’s location, condition, services, and staff attitude were considered factors to choose the services. Conclusion: Living in an urban area does not guarantee the family caregivers have better knowledge and good healthcare-seeking behavior. Therefore, nurses should provide comprehensive education about pneumonia, its symptoms, and treatment management to improve family care and prevent pneumonia-related deaths. Integrated management of children with illness is recommended to help the family caregivers of children with pneumonia receive treatment as quickly as possible.